A Comprehensive Review on Pharmacotherapeutics of Herbal Bioenhancers. (17th September 2012) - Dudhatra, Ghanshyam B.; Mody, Shailesh K.; Awale, Madhavi M.; Patel, Hitesh B.; Modi, Chirag M.; Kumar, Avinash; Kamani, Divyesh R.; Chauhan, Bhavesh N.
Abstract : In India, Ayurveda has made a major contribution to the drug discovery process with new means of identifying active compounds. Recent advancement in bioavailability enhancement of drugs by compounds of herbal origin has produced a revolutionary shift in the way of therapeutics. Thus, bibliographic investigation was carried out by analyzing classical text books and peer-reviewed papers, consulting worldwide-accepted scientific databases from last 30 years. Herbal bioenhancers have been shown to enhance bioavailability and bioefficacy of different classes of drugs, such as antibiotics, antituberculosis, antiviral, antifungal, and anticancerous drugs at low doses. They have also improved oral absorption of nutraceuticals like vitamins, minerals, amino acids, and certain herbal compounds. Their mechanism of action is mainly through absorption process, drug metabolism, and action on drug target. This paper clearly indicates that scientific researchers and pharmaceutical industries have to give emphasis on experimental studies to find out novel active principles from such a vast array of unexploited plants having a role as a bioavailability and bioefficacy enhancer. Also, the mechanisms of action by which bioenhancer compounds exert bioenhancing effects remain to be explored.